(untitled) (Journal of Comilla Medical College Teachers’ Association, 2024)
Background: Dengue fever, caused by a mosquito-borne arbovirus, is characterized by painful febrile symptoms. Hematological abnormalities are frequently observed, especially in patients testing positive for NS1 antigen. NS1 antigen, a protein generated by the dengue virus during acute infection, is detectable in the blood of infected individuals. This study aimed to assess the pattern of hematological abnormalities in NS1-positive dengue patients. Methods: This prospective cross-sectional study was conducted in the Department of Medicine, Comilla Medical College, Cumilla, Bangladesh from July 2022 to June 2023. A total of 137 dengue patients who tested positive for NS1 were included as study subjects, selected through purposive sampling. Data processing and analysis were conducted using Office tools. Results: In this study, among our total participants, the mean ±SD hemoglobin was 13.2±1.8 g/dl, hematocrit was 39.4±5.4%, leucocyte count was 7.7±5.8 x109/L, neutrophil count was 5.5±1.3 x109/L, and lymphocyte count was 3.7±1.2 x109/L, all of which were within normal ranges. However, the mean ±SD platelet level was found to be 98.1±58.1 x109/L, which was abnormally lower. Conclusion: Among NS1-positive dengue patients, hematological assessment reveals normal levels of hemoglobin, hematocrit, leucocytes, neutrophils, and lymphocytes. Although the mean hematocrit value is typically normal, a significant number of cases show values either higher or lower than the normal range. However, platelet levels are notably lower. J Com Med Col Teachers Asso July 2024; 28(2): 82-86